Profil Computational Thinking Dalam Menyelesaikan Soal HOTS Matematika - Else Sendi Anggraeny; Reva Oktrias Amanda; Adelia Selviana; Ghanesa Rizal Monacco; Reyta Tri Ayuningtyas; Yessi Kusuma Wardani; Rissa Prima Kurniawati (Universitas PGRI Madiun, 2026)
This study aims to describe the Computational Thinking (CT) profiles of elementary school students in solving higher-order thinking skills (HOTS) math problems on the topic of plane figures. The study employed a descriptive qualitative approach with five fifth-grade students selected through purposive sampling. Data were collected through tests, observations, and documentation, then analyzed based on four indicators of Computational Thinking: decomposition, pattern recognition, abstraction, and algorithmic thinking. The results showed that most students were able to perform decomposition and algorithmic thinking but still struggled with pattern recognition and abstraction, which affected the accuracy of their problem-solving. These findings suggest that mathematics instruction needs to develop computational thinking skills so that students’ higher-order thinking and problem-solving abilities can be further optimized.